Modified/Unmodified Nanoparticle Adsorbents of Cellulose Origin With High Adsorptive Potential for Removal of Pb(II) From Aqueous Solution - Yakubu, Azeh; Olatunji, Gabriel Ademola; Adekola, Folahan Amoo (European Scientific Journal, ESJ, 2017)
This investigation was conducted to evaluate the adsorption capacity of nanoparticles of cellulose origin. Nanoparticles were synthesized by acid hydrolysis of microcrystalline cellulose/cellulose acetate using 64% H3PO4 and characterized using FTIR, XRD, TGA-DTGA, BET and SEM analysis. Adsorption kinetics of Pb (II) ions in aqueous solution was investigated and the effect of initial concentration, pH, time, adsorbent dosage and solution temperature. The results showed that adsorption increased with increasing concentration with removal efficiencies of 60% and 92.99% for Azeh2 and Azeh10 respectively for initial lead concentration of 3 mg/g. The effects of contact time showed that adsorption maximum was attained within 24h of contact time. The maximum adsorption capacity and removal efficiency were achieved at pH6. Small dose of adsorbent had better performance. The kinetics of adsorption was best described by the pseudo-second-Order model while the adsorption mechanism was chemisorption and pore diffusion based on intra-particle diffusion model. The isotherm model was Freundlich. Though, all tested isotherm models relatively showed good correlation coefficients ranging from 0.969-1.000. The adsorption process was exothermic for Azeh-TDI, with a negative value of -12.812 X 103 KJ/mol. This indicates that the adsorption process for Pb by Azeh-TDI was spontaneous. Adsorption by Azeh2 was endothermic in nature.